GAYA BELAJAR DAN HUBUNGANNYA DENGAN HASIL BELAJAR BIOLOGI SISWA MADRASAH ALIYAH NEGERI DI ERA COVID- 9 (Universitas PGRI Sumatera Barat, 2022)
This study aims to describe learning styles and their relationship to biology learning outcomes for students of class XI IPA Madrasah Aliyah Negeri (MAN) in the era of covid-19. This type of research is descriptive quantitative research. The learning styles studied include visual, auditory and kinesthetic learning styles. Sampling was done by total sampling with a total sample of 68 students of class XI IPA. The research instrument was a questionnaire on the types of student learning styles that were valid and reliable. The results of the validity test of the questionnaire by two validators were 3.25 and 3.00, respectively, with a valid and appropriate category for use, and the results of the questionnaire reliability test were obtained at 0.66 with a fairly high interpretation. The results showed that the overall student learning style was kinesthetic by 41%; auditory 30% and visual 29%, the highest learning style is kinesthetic. There is a positive relationship between learning styles and student biology learning outcomes. It can be concluded that the higher the percentage of learning styles, the higher the students biology learning outcomes. The results of this study provide information to teachers to use appropriate and varied strategies and methods as well as learning media during the learning process.